Problems of the Citizenship Institute in the Russian Federation - A. A. Nepomnyashchaya (Сибирское юридическое обозрение, 2013)
The article deals with the definition of the essence and importance of citizenship. The author considers different scientific concepts concerning the definitions of the citizenship notion as well as the peculiarities of the citizenship, representing one of the types of relations governed by law – legal state of a person in citizenship.